Применим формулы сокращенного умножения:
а) (a + b)² = a² + 2·a·b + b²
б) (a - b)² = a² - 2·a·b + b²
в) (a + b)·(a - b) = a² - b²
1. (x–3)² – 2·x² = 9 – (x+1)²
x² – 6·x + 9 – 2·x² = 9 – (x² + 2·x + 1)
–6·x + 9 – x² – 9 = – x² – 2·x – 1
–6·x – x² + x² + 2·x = – 1
– 4·x = – 1
x = 1/4.
2. (x⁴ – 3)·(x⁴ + 3) – (x⁴ – 5)² = x⁸ – 9 – (x⁸ – 10·x⁴ + 25) =
= x⁸ – 9 – x⁸ + 10·x⁴ – 25 = 10·x⁴ – 34.
При x = 3
10·3⁴ – 34 = 10·81 – 34 = 810 – 34 = 776.
3. (3·a + 2·b)² · (3·a – 2·b)² = ((3·a + 2·b) · (3·a – 2·b))² =
= (9·a² – 4·b²)² = 81·a⁴ – 72·a²·b² + 16·b⁴.
ОДЗ:
+ - +
---------(0)----------(3)-------------
/////////// ////////////////
∈ ∞ ∪ ∞
ответ:
ОДЗ:
Замена:
или
или
или
ответ:
ОДЗ:
+ - +
---------(-2)----------(0)-------------
/////////// ////////////////
∈ ∞ ∪ ∞
+ - +
----------(-3)-----------(1)--------------
/////////////////
С учётом ОДЗ получаем
ответ: ∪
ОДЗ:
С учётом ОДЗ получаем
ответ: